Hume’s Theory of Business Ethics Revisited - Kline, William (2012)
Hume’s examination of the conventions of property, trade, and contract addresses the moral foundations that make business possible. In this light, Hume’s theory of justice is also a foundational work in business ethics. In Hume’s analysis of these conventions, both philosophers and game theorists have correctly identified “proto” game-theoretic elements. One of the few attempts to offer a Humean theory of business ethics rests on this game-theoretic interpretation of Hume’s argument. This article argues that game-theoretic reasoning is only one part of a Humean business ethics and this can be shown by further analyzing Hume’s theory of justice. As we examine his theory, it becomes clear that Hume is not trying to show how it is always rational to respect the rules of business. Hume is not engaging in, or attempting, a reconciliation project and neither is a Humean business ethics. The final section of the article is a brief Humean analysis of the effectiveness of codes of ethics. The purpose of this section is not to decide the issue but to show how a Humean approach is both useful, relevant, and involves more than reconciling rationality and morality.
Keywords: Sensible knave; Self-interest; Reconciliation project; Justice; Humean business ethics; Hume; Game Theory; Convention; Compliance; codes of ethics